“No poo” e “low poo”: um estudo netnográfico sobre anticonsumo e resistência - Silva, Brena Carolina de Oliveira (2020)
This research aimed to understand how the processes of anti-consumption and resistance are configured in a community that brings together adepts of "no-poo" and "low-poo" techniques. For this, were made participant and non-participant observations in Facebook's “No and Low Poo Beginners” community, between November 2018 and September 2019, followed by semistructured interviews for the triangulation of the collection. For the analysis, were used resources from discourse analysis and computer-mediated discourse analysis. The results of the research showed that anti-consumption occurs since the beginning of adherence to these techniques, and it is practiced against some types of shampoos or all this category of products. Being against the consumption did not cancel the relationship with the market. Thus, the adepts showed behaviors like excessive consumption and reduced consumption when practicing rejection. When in the collective environment, some supporters showed resistance behaviors, such as political manifestations, while others began to consume excessively. Due to the characteristics of this community and its history, it was characterized as a place of anti-consumption and resistance that has become a consumption environment. The limiting factors of this research were the overlapping concepts of resistance to consumption and anti-consumption mentioned in the literature and the number of interviews made. However, it was possible to respond to the objectives, establishing the consumption behavior of supporters in the virtual community. It contributed to studies in the area, understood the concepts of anti-consumption and resistance from a new perspective, and characterized a community dedicated to the theme.